Long term transvenous ventricular pacing in adults with congenital abnormalities of the heart and great arteries. Issue 4 (October 1983) - Ward, D E; Clarke, B; Schofield, P M; Jones, S; Dawkins, K; Bennett, D
Abstract : Improved techniques of transvenous pacing have made it possible to use this approach in various congenital cardiac abnormalities. Transvenous active fixation pacing leads were implanted in seven patients aged 15 to 81 years with abnormal venous, atrioventricular, or ventriculoarterial connections with successful ventricular pacing.